2004
DOI: 10.1016/s0014-5793(04)00066-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of GR‐mediated transcription by p23 requires interaction with Hsp90

Abstract: p23 is a regulatory co-chaperone of heat shock protein (Hsp) 90, but can also act as a general molecular chaperone by itself. Using novel point mutations of p23 that disrupt its interaction with Hsp90 we found its co-chaperone function to be required for its inhibitory e¡ect on glucocorticoid receptor (GR). The C-terminal region of p23, which is required for its chaperone activity, is dispensable for inhibition of GR. Importantly, similar results were obtained with a constitutively active GR. Thus, the action … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…Consistent with our studies of primary embryonic fibroblasts, decreased GR activity secondary to loss of cPGES/p23 would result in loss of this inhibitory pathway, resulting in an increase in PGE 2 and other COX-2-dependent metabolites. Transfection of cell lines with p23 expression vectors has been reported, similar to loss of cPGES/p23, to result in inhibition of GR activity in cells lines (16,73). This raises the possibility that the increased PGE 2 production noted in cells transfected with cPGES/p23 was the indirect consequence of decreased GR function in this line.…”
Section: Discussionmentioning
confidence: 93%
“…Consistent with our studies of primary embryonic fibroblasts, decreased GR activity secondary to loss of cPGES/p23 would result in loss of this inhibitory pathway, resulting in an increase in PGE 2 and other COX-2-dependent metabolites. Transfection of cell lines with p23 expression vectors has been reported, similar to loss of cPGES/p23, to result in inhibition of GR activity in cells lines (16,73). This raises the possibility that the increased PGE 2 production noted in cells transfected with cPGES/p23 was the indirect consequence of decreased GR function in this line.…”
Section: Discussionmentioning
confidence: 93%
“…2A and those using purified recombinant proteins may be due to the fact that p23 can exist in a complex with HSP90 within the cell and that the p23⅐HSP90 complex might interact differently with WT as compared with D4E/C127S PHD2. Previous studies showed that a W106A mutant of p23 is defective in its interaction with HSP90 (34). We therefore tested the role of HSP90-mediated binding by examining the ability of W106A p23 to coimmunoprecipitate PHD2.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmids-The plasmids MTVLuc, green fluorescence protein (GFP)-GR, and pCMV␤-Gal have been described previously (33). All immunophilins and dynamitin were cloned downstream of the CMV promoter of the vector pRK5MCS.…”
Section: Methodsmentioning
confidence: 99%